Antifouling polymeric nanocomposite membrane based on interfacial polymerization of polyamide enhanced with green TiO2 nanoparticles for water desalination - Abu-Dalo,Muna A.; Bozeya,Ayat; Sawalmeh,Zaid; Albiss,Borhan; Alnairat,Nour; Abu-Zurayk,Rund (PeerJ Analytical Chemistry, 2023)
In the present investigation, the preparation and characterization of polyamide/TiO2 as thin film nanocomposites (TFN) for brackish water desalination was investigated. TiO2 nanoparticles (NPs) were synthesized by a green method using thyme plant extract as a reducing and capping agent. The TiO2 NPs was successfully prepared in pure crystalline anatase phase with 15 nm size, and −33.1 mV zeta potential. The antimicrobial tests confirmed the antimicrobial activity of TiO2 against gram-positive and gram-negative bacteria. In addition, TiO2 NPs showed a good photocatalytic activity in degradation of methylene blue dye. TFN based on interfacial polymerization was enhanced by embedding 5% of the greenly synthesized TiO2 NPs within the polyamide thin film active layer. The incorporation of TiO2 NPs was confirmed by SEM, atomic force microscope (AFM), surface wettability, and FTIR. Membranes performance was investigated based on flux, salt rejection and fouling resistance. The antifouling was examined using bovine serum albumin (BSA) as protein fouling by dead-end cell filtration system at 2 bar. The results showed the TFN increased in water flux by 40.9% and a slight decrease in NaCl rejection (6.3%) was observed, with enhancement in antifouling properties. The flux recovery rate of the modified TFN membranes after fouling with BSA solution was enhanced by 21.5% (from 61.7% for TFC to 83.2% for TFN). Also, they demonstrated remarkable anti-biofouling behavior against both bacterial strains.
Keywords: Polymeric nanocomposite membrane; TiO2 nanoparticles; Antifouling; Interfacial polymerization; Polyamide